Urban setting: induce or reduce mental health? - Low, Bee Teng; Sharif, Roslina; Wan Ishak, Wan Sofiah; Kozlowski, Marek; Ismail, Sumarni (Universiti Putra Malaysia Press, 2018)
This paper presents and reviews various literature and scholarly studies regarding the effect of globalisation and developments in urban areas which causes mental health issues. It is aimed to provide a comprehensive understanding on the current knowledge in the field of mental health problems particularly at the early stages of stress. This study utilises qualitative content analysis method which focuses on reviewing and summarizing literatures such as papers, journals, articles and books related to urbanization and mental health. The further analysis shall then conclude the relationship between urban setting and stress in Malaysia, as well as the stigma that is attached to it which may resulted in mental deterioration where a new design intervention is required. Hence the proposal for a therapeutic environment particularly in relieving early stages of stress is essential.